Impact of ICT diffusion and financial development on economic growth in developing countries - Verma, Anushka; Sandeep Dandgawhal, Prajakta; Kumar Giri, Arun (Universidad ESAN. ESAN Ediciones, 2023)
Purpose: The present study aimed to examine the relationship between information and communication technologies (ICT) diffusion, financial development and economic growth in the panel of developing countries for 2005–2019. Design/methodology/approach: The study employed the principal component analysis (PCA) to extract the index of ICT diffusion. First-generation panel unit root tests such as Levine Lin Chu (LLC), Im Pesaran Shin (IPS), Augmented Dickey-Fuller (ADF) and Phillips and Perron (PP) were employed to check the stationarity of the variables. Pedroni and Kao co-integration techniques were used to examine the existence of the long-run relationship, and co-integration coefficients were estimated using FMOLS and dynamic ordinary least squares (DOLS). The panel Granger causality approach examined the short-run and long-run causality. Findings: The results confirmed that ICT diffusion, financial development and trade openness accelerate growth, whereas inflation dampens economic growth. Further, the causality test showed bidirectional causality between ICT growth and financial development growth but a unidirectional causality from financial development to ICT diffusion in developing countries. Originality/value: The study recommends synchronizing public and private sector investment for a synergistic effect on ICT infrastructure and adequate investment in the financial sector to increase the growth rate in developing countries. Economic policies should be adopted toward incentives and subsidies to ensure affordable ICT services for disadvantaged communities. Also, training programs focussing on enhancing digital literacy to enable all segments of the population to use digital platforms for financial services are recommended.

Objetivo: El presente estudio tuvo como objetivo examinar la relación entre la difusión de las tecnologías de la información y la comunicación (TIC), el desarrollo financiero y el crecimiento económico en el panel de países en desarrollo para el período 2005-2019. Diseño/metodología/enfoque: El estudio empleó el análisis de componentes principales (ACP) para extraer el índice de difusión de las TIC. Se emplearon pruebas de raíz unitaria de panel de primera generación como Levine Lin Chu (LLC), Im Pesaran Shin (IPS), Augmented Dickey-Fuller (ADF) y Phillips y Perron (PP) para verificar la estacionariedad de las variables. Se utilizaron técnicas de cointegración de Pedroni y Kao para examinar la existencia de la relación de largo plazo, y los coeficientes de cointegración se estimaron utilizando FMOLS (Mínimos cuadrados completamente modificados) y mínimos cuadrados ordinarios dinámicos (DOLS). El enfoque de causalidad del panel de Granger examinó la causalidad a corto y largo plazo. Hallazgos: Los resultados confirmaron que la difusión de las TIC, el desarrollo financiero y la apertura comercial aceleran el crecimiento, mientras que la inflación frena el crecimiento económico. Además, la prueba de causalidad mostró una causalidad bidireccional entre el crecimiento de las TIC y el crecimiento del desarrollo financiero, pero una causalidad unidireccional entre el desarrollo financiero y la difusión de las TIC en los países en desarrollo. Originalidad/valor: El estudio recomienda sincronizar la inversión de los sectores público y privado para lograr un efecto sinérgico en la infraestructura de TIC y una inversión adecuada en el sector financiero para aumentar la tasa de crecimiento en los países en desarrollo. Se deben adoptar políticas económicas orientadas a incentivos y subsidios para garantizar servicios de TIC asequibles para las comunidades desfavorecidas. Además, se recomiendan programas de capacitación centrados en mejorar la alfabetización digital para permitir que todos los segmentos de la población utilicen plataformas digitales para servicios financieros.
Keywords: Developing countries; ICT diffusion; Financial development; Países en desarrollo; Economic growth; Difusión de las TIC; Desarrollo financiero; Panel data; Crecimiento económico; FMOLS; Datos de panel; FMOLS; DOLS; DOLS; https://purl.org/pe-repo/ocde/ford#5.02.04